Pengaruh pelatihan pengolahan hasil ubi kayu dan ubi jalar di Balai Besar Pelatihan Pertanian Ketindan terhadap peningkatan kinerja penyuluh pertanian - Murdani Murdani; Dewi Melani (Fakultas Pertanian Universitas Yudharta Pasuruan, 2021)
This study aims to determine the effect of training on processing cassava and sweet potato products held at the Indonesia Centre for Agricultural Training (ICAT) of Ketindan and determine the correlation between the participants' areas of origin on improving the performance of agricultural instructors. This research method uses data sources that come from the field obtained by interviewing alumni, fostered farmers, colleagues, and alumni superiors with a survey using a questionnaire. The results of the data were analyzed descriptively and correlated using SPSS Software Version 18 for Windows. The general research results show that the training that has been carried out in 2014, 2015, and 2017 has an effect on increasing the performance of agricultural instructors by 63.20%. This is measured by 3 (three) indicators, namely 1) preparation of agricultural extension by 3.40 or 68.00%; 2) implementation of agricultural extension 2.77 or 55.40%; and 3) evaluation and reporting of 3.29 or 65.80%. The results of the correlation between the participants' regions of origin and the performance of the extension workers showed that the highest performance achievement was 77 and the lowest was 26. Thus, the extension workers could show good performance in disseminating the application of technological innovations for processing cassava and sweet potato products to farmers or their fostered business actors which affected increasing cassava and sweet potato production and productivity.